Connecting the dots : Computational network analysis for disease insight and drug repurposing - Siminea, Nicoleta; Czeizler, Eugen; Popescu, Victor-Bogdan; Petre, Ion; Păun, Andrei (Elsevier, 2025)
Network biology is a powerful framework for studying the structure, function, and dynamics of biological systems, offering insights into the balance between health and disease states. The field is seeing rapid progress in all of its aspects: data availability, network synthesis, network analytics, and impactful applications in medicine and drug development. We review the most recent and significant results in network biomedicine, with a focus on the latest data, analytics, software resources, and applications in medicine. We also discuss what in our view are the likely directions of impactful development over the next few years.